Auriculotherapy used to manage orthodontic pain: a randomized controlled pilot study - Emanuela SERRITELLA; Alessandra IMPELLIZZERI; Aldo LIGUORI; Gabriella GALLUCCIO (Dental Press Editora, 2021)
ABSTRACT Introduction: Several methods are commonly used to decrease orthodontic pain, but versatile tools and standardized protocols are still lacking. Objective: In response to the need for alternatives to conventional analgesic methods, this study evaluates the analgesic effects of auriculotherapy (AT) during the first three months of fixed orthodontic treatment. Methods: A sample of 36 subjects was selected, with patients randomly allocated into two homogeneous groups, Study Group (SG) and Control Group (CG), depending on the application/non-application of AT. Patients rated their pain scores monthly from 0 to 10, on visual analogue scales (VAS) at the time of bonding (T0) and again at two appliance adjustments (T1 and T2). At each of these treatment phases, VAS was applied in six different time moments (TM): immediately before, immediately after, after 4 hours, after 8 hours, after 24 hours, and after 72h hours. Descriptive statistical analysis, a Student's t-test, and a Chi-square test were applied to the collected data (statistical significance for p< 0.05). Results: SG patients reported lower pain levels than CG patients, both at T0, T1 and T2. Moreover, average pain intensity values were lower in the SG for all TM analyzed, with the t-test significant (p< 0.05) for most TMs. Conclusion: AT was effective in the pain treatment of patients with fixed orthodontic appliances. Further studies are needed with a sham control group to confirm the validity of these results.